Taxonomic notes on the ant-eating spider genera Asceua Thorell, 1887 and Cydrela Thorell, 1873 from India, with comment on Indian species of Euryeidon Dankittipakul & Jocqué, 2004 (Araneae: Zodariidae) - Sankaran, Pradeep M. (Zootaxa, 2023)
Indian species of the ant-eating spider genera Asceua Thorell, 1887, Cydrela Thorell, 1873 and Euryeidon Dankittipakul & Jocqué, 2004 are reviewed. The species Asceua cingulata (Simon, 1905) is redescribed and illustrated based on type and freshly collected material and a new species, A. thrippalurense sp. nov. is described and illustrated based on both sexes. All the Indian Cydrela species are transferred back to the genus Capheris Simon, 1893 under which these were originally placed. The species Capheris escheri Reimoser, 1934 comb. rest. and Caph. stillata Simon, 1905 comb. rest. are redescribed and illustrated, the former based on its type specimen, while the latter based on freshly collected material. The species Capheris nitidiceps Simon, 1905 comb. rest. is considered as a nomen dubium due to the immature stage of the holotype. The two Indian species of Euryeidon are transferred to the genus Laminion Sankaran, Caleb & Sebastian, 2020 due to generic similarities. The distribution of all these species is mapped.